Semantic Study: Analysis of References for Animal as Object in Animal Related Articles from Internet - Kartikasari Dwi Rokhmah (Universitas Gadjah Mada, 2012)
Analyzing the reference for particular object is appropriate in the study of text. This paper discusses the reference for animal in internet articles. The data sources are twenty articles with animal topics. They are taken from news.nationalgeographic.com and animal.discovery.com. The method is library research to collect qualitative findings. The analysis is on the use of reference and the factors that influence the use of reference. The findings show that the dominant reference she (n: 119; 40.8%) is influenced by the gender and singularity. In addition, the frequency of references he (n: 70; 23.9%), it (n: 41; 14.1%) and they (n: 62; 21.2%) are influenced by gender, singularity, plurality, association and writer’s attitude. However association and writer’s attitude factor is not conclusive for this study.